Calculation of the effective external dose rate to a person staying in the resettlement zone of the Vetka district of the Gomel region of Belarus based on in situ and ex situ assessments in 2016–2018. (April 2020) - Ramzaev, V.; Bernhardsson, C.; Dvornik, A.; Barkovsky, A.; Vodovatov, A.; Jönsson, M.; Gaponenko, S.
Abstract: The aim of this study was to perform a preliminary assessment of the expected effective dose rate from external exposure to an adult individual staying at that part of the radioactively contaminated territory of the Vetka district of the Gomel region of the Republic of Belarus, from where residents had been resettled after the Chernobyl accident. For this assessment, in summer 2016 and 2018 soil samples were taken from 19 sites located in forests (7 plots), virgin meadows (4 plots), cultivated meadows (6 plots) and vegetable gardens (2 plots), with the subsequent estimation of the inventory and vertical distribution of 137 Cs in the soil. The values of 137 Cs inventory in the soil ranged from 452 to 1620 kBq m −2 (mean = 904 kBq m −2, median = 964 kBq m −2 ). The results of the measurement of soil samples were used to calculate values of the air kerma rate, normalized to the inventory of radioactive caesium in the soil. On average, the normalized indicator of the air kerma rate from the man-made source was higher in forests (1.13 nGy h −1 per kBq m −2 ) compared to virgin meadows (0.95 nGy h −1 per kBq m −2 ). Normalized air kerma rate in cultivated meadows and vegetable gardens was approximately two times lower than the corresponding indicator for virgin meadows. Using a field gamma spectrometer-dosemeter, ambient dose equivalent rate of gamma radiation in the air was measured at the surveyed sites and the contributions of the technogenic and natural components to the dose rate were estimated. Additionally, such measurements were performed on asphalted surfaces (5 sites) and inside two wooden houses. The measured values of the total ambient dose equivalent rate at a height of 1 m above the ground, asphalted surface or house floor varied from 160 to 2260 nSv h −1 . The lowest levels were recorded over asphalted surfaces and inside houses, and the highest ones at forest and virgin meadow sites. The contribution of the technogenic component to the total dose rate varied from 61.9% to 98.8% (mean = 88.9%; n = 26). The effective dose of anthropogenic radiation calculated from the results of in situ measurements in a forest, virgin meadow, cultivated meadow, kitchen garden, asphalted area and house was 0.59, 0.80, 0.34, 0.29, 0.06 and 0.06 μSv h −1, respectively. Similar values for land plots were calculated based on ex situ analysis of soil samples. It can be expected that, starting from 2020, the average effective external dose of a person staying in the resettlement zone of the Vetka district will not exceed 1 mSv year −1 . Highlights: A study in the resettlement zone of Belarus in 2016–2018. Inventory and vertical distribution of 137 Cs in soil. Measured and calculated gamma dose rates in air. Assessments of effective external dose for a fictive adult individual. The expected dose from 137 Cs to the individual will be less than 1 mSv per year.